Foucault and literature : towards a genealogy of writing - During, Simon (Routledge, 1992)
The writings of the French historian, literary critic and philosopher Michel Foucault have been of immense importance to developments in literary studies since the late 1970s. He, more than anyone, stands behind the new historicism' and cultural materialism' that currently dominate international literary studies. Simon During provides a detailed introduction to the whole body of Foucault's work, with a particular emphasis on his literary theory. His study takes in Foucault's early studies of transgressive' writing from Sade and Artaud to the French new novellists' of the 1960s, and his later concern with the genealogy of the author/intellectual, writing and theorizing within specific, historical mechanisms of social control and production. Foucault and Literature offers a critique both of Foucault and of the literary studies that have been influenced by him, and goes on to develop new methods of post-Foucauldian literary/cultural analysis.